High Spatial Resolution Multi-Organ Finite Element Modeling of Ventricular-Arterial Coupling - Shavik, Sheikh Mohammad; Jiang, Zhenxiang; Baek, Seungik; Lee, Lik Chuan (Frontiers in Physiology, 2018)
While it has long been recognized that bi-directional interaction between the heart and the vasculature plays a critical role in the proper functioning of the cardiovascular system, a comprehensive study of this interaction has largely been hampered by a lack of modeling framework capable of simultaneously accommodating high-resolution models of the heart and vasculature. Here, we address this issue and present a computational modeling framework that couples finite element (FE) models of the left ventricle (LV) and aorta to elucidate ventricular - arterial coupling in the systemic circulation. We show in a baseline simulation that the framework predictions of (1) LV pressure - volume loop, (2) aorta pressure - diameter relationship, (3) pressure - waveforms of the aorta, LV and left atrium (LA) over the cardiac cycle are consistent with the physiological measurements found in healthy human. To develop insights of ventricular-arterial interactions, the framework was then used to simulate how alterations in the geometrical or, material parameter(s) of the aorta affect the LV and vice versa. We show that changing the geometry and microstructure of the aorta model in the framework led to changes in the functional behaviors of both LV and aorta that are consistent with experimental observations. On the other hand, changing contractility and passive stiffness of the LV model in the framework also produced changes in both the LV and aorta functional behaviors that are consistent with physiology principles.